A review on the assessment of drought index / Raja Muhammad Naufal Raja Azman ... [et al.] - Raja Azman, Raja Muhammad Naufal; Mohd Noor, Nur Asmaliza; Abdullah, Sharifah; Mohamed, Marini (Universiti Teknologi MARA, Pahang, 2022)
The climate change interference and the increase of surface temperature have contributed towards the changes in the atmosphere that give significant effects on the availability of water. Drought is a phenomenon closely related to water quantity issues, and usually has influences on the society. This paper reviews the six available drought indices that can contribute towards the development of drought indices for Malaysia. Each index has its own variables, advantages and disadvantages. To conduct the analysis, the selection of indices should be subjected to the availability of data for that particular area. This review will benefit water engineers by providing information on the development of drought index for long term water management plans as drought management can be planned at early stage. Thus, the mitigation strategies can be devised to address the impact, especially on agriculture and water supply in Malaysia.